Functional analysis of NtPDX2 in Nicotiana tabacum L. associated with stem development - Xu, Li; Cui, Yuxin; Xing, Jiaxin; Mi, Qili; Wang, Zhixing; Wang, Xujing; Zeng, Wanli; Xiang, Haiying; Jiang, Jiarui; Deng, Lele; Wang, Kunmiao; Yang, Jiangtao; et al. (Frontiers in Plant Science, 2025)
Vitamin B6 is a water-soluble vitamin that is essential for all living organisms in their life activities. Among its forms, pyridoxal 5’-phosphate (PLP) is the primary metabolically active form of Vitamin B6, which usually plays a crucial role in the metabolism of proteins, fatty acids, and carbohydrates. To date, although the molecular functions of genes involved in vitamin B6 biosynthesis, including Pdx1, Pdx2, Pdx3, and Sos4, have been reported in various plants, no studies have yet explored the functions of NtPDX1 and NtPDX2 in tobacco. This study used the Nicotiana tabacum L. as material to clone the CDS sequence of the NtPDXs. Through bioinformatics analysis, we predicted the phylogenetic relationships and functions of these genes; the subcellular localization of NtPDX2 was found to be in the cytoplasmic structures. By conducting both constitutive overexpression and homozygous knockout studies of the NtPDX2, we observed a significant increase in vitamin B6 content in the stem tissues of overexpressing plants (up to 150%), while knockout plants showed a decrease to 60%. This led to changes in agronomic traits such as plant height and stem thickness in tobacco plants. The overexpressing plants exhibited a significant increase in height (100.93 cm) and stem thickness (13.64 cm), whereas the knockout plants were shorter in height (73.10 cm) and had thinner stems (10.83 cm). By integrating transcriptome sequencing technology with molecular biology methods, we aim to elucidate the molecular mechanisms underlying the role of NtPDX2 in tobacco growth and development, thereby providing new genetic resources and a theoretical foundation for the cultivation of new tobacco varieties with superior quality for flue-cured tobacco.